2011
DOI: 10.1264/jsme2.me11116
|View full text |Cite
|
Sign up to set email alerts
|

Community Variability of Bacteria in Alpine Snow (Mont Blanc) Containing Saharan Dust Deposition and Their Snow Colonisation Potential

Abstract: Microorganisms uplifted during dust storms survive long-range transport in the atmosphere and could colonize highaltitude snow. Bacterial communities in alpine snow on a Mont Blanc glacier, associated with four depositions of Saharan dust during the period 2006-2009, were studied using 16S rRNA gene sequencing and flow cytometry. Also, sand from the Tunisian Sahara, Saharan dust collected in Grenoble and Mont Blanc snow containing no Saharan dust (one sample of each) were analyzed. The bacterial community comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 54 publications
3
27
1
Order By: Relevance
“…An additional important input of microorganisms is from far territories, such as the arid Sahara desert in the case of the European Alps (Kellogg and Griffin 2006). Sandy storms from the Sahara to alpine glaciers carry several types of microbial cells, both in viable and quiescent form (Chuvochina et al 2011(Chuvochina et al , 2012. These cells are physically attached to and protected by microparticles of clay-sized minerals, such as illite and smectite.…”
Section: Colonization Of Glacier Surface By Microorganismsmentioning
confidence: 99%
“…An additional important input of microorganisms is from far territories, such as the arid Sahara desert in the case of the European Alps (Kellogg and Griffin 2006). Sandy storms from the Sahara to alpine glaciers carry several types of microbial cells, both in viable and quiescent form (Chuvochina et al 2011(Chuvochina et al , 2012. These cells are physically attached to and protected by microparticles of clay-sized minerals, such as illite and smectite.…”
Section: Colonization Of Glacier Surface By Microorganismsmentioning
confidence: 99%
“…Mineral debris released after glacier retreat is exposed to continuous atmospheric input (exogenous source) of microbes (Womack et al, 2010) through precipitations (Zhang et al, 2010;Šantl-Temkiv et al, 2012) and dry deposition, such as wind-blown dust and plant debris (Chuvochina et al, 2011;Bowers et al, 2012;DeLeon-Rodriguez et al, 2013). The atmosphere in particular is often wrongly considered sterile because of harsh ultraviolet (UV) radiation and extreme C and nutrient limitations (Womack et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While N 2 fixation appears to be a relatively unconserved microbial trait (genus to species level; Martiny et al, 2015), the prevalence of this phylotype and its similarity with A. siamensis suggests that there may be the genetic potential for N 2 fixation in this environment. Previous studies suggested that snow-associated microbial communities are largely derived from eolian movement and deposition of microorganisms (Bowers et al, 2012;Chuvochina et al, 2011b). Windborne dust is one primary vector of such movement, although aerosolized microorganisms do not necessarily require association with dust particles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recovered four lesser abundant genera (Methylobacterium, Geodermatophilus, Hymenobacter, and Janthinobacterium) that are known to survive in the cryosphere (Chuvochina et al, 2011a;Kim et al, 2012b;Rainey et al, 2005). The first three genera can tolerate high doses of ionizing radiation (Chuvochina et al, 2011b;Rainey et al, 2005), while the fourth is a genus that contains psychrotolerant bacteria (Segawa et al, 2005). Burkholderia, a genus comprised of bacteria found in polar environments and that dominate some subalpine soils (Lipson et al, 2008), was also found in the snowpack, albeit at a low relative abundance (0.15%-0.45% of sequences in upper and lower layers of snow, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation